Peningkatan Pergaulan Sehat dan Kesehatan Reproduksi Remaja di Kabupaten Semarang - Datik Wahyuningsih; Halilintar Ivan Chrisnanto; Agustina Bidadari Maharani Putri; Indriana Laras Asri; Devina Nesie Permatadita; Sandra Puspita Dyah Anggraeni; Sapto irawan Irawan (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2026)
Healthy relationships & reproductive health are crucial issues that need serious attention, especially among teenagers. Lack of understanding of this aspect can lead to various problems, e.g. unwanted pregnancies and the spread of sexually transmitted diseases. This socialization activity aims to increase awareness and knowledge of teenagers regarding the importance of healthy relationships and reproductive health through a Project Based Learning. The socialization was carried out in Desa Purworejo, Kecamatan Suruh, Kabupaten Semarang by involving village midwives, heads, and officials as the main companions in shaping the mindset and behavior of teenagers related to issues. The methods used include interactive counseling, group discussions, and experience based activities, such as educational games and digital content creation. The results of the activity showed an increase in participants understanding of the topics presented, a change in attitudes that were more positive, contributed to the development of life skills, communication skills, leadership, and teamwork.